2021
DOI: 10.1108/ijoem-05-2020-0567
|View full text |Cite
|
Sign up to set email alerts
|

Systemic risk in ASEAN-6: a new empirical investigation

Abstract: PurposeThe authors provide a comprehensive study on systemic risk of the banking sectors in the ASEAN-6 countries. In particular, they investigate the systemic risk dynamics and determinants of 49 listed banks in the region over the 2000–2018 period.Design/methodology/approachThe authors employ the market-based SRISK measure of Brownlees and Engle (2017) to investigate the systemic risk of the ASEAN-6's banking sectors.FindingsThe authors find that the regional systemic risk fluctuates significantly and curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…Some banks became relatively "too big" to systemically influence others. e study by Le [30], by applying the same measure to the banking sector of 6 ASEAN economies, has found that systemic risk is linked to size, quality of the loan, and market to book value. Banks experienced strong regional connectedness rather than the one experienced during the time of GFC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some banks became relatively "too big" to systemically influence others. e study by Le [30], by applying the same measure to the banking sector of 6 ASEAN economies, has found that systemic risk is linked to size, quality of the loan, and market to book value. Banks experienced strong regional connectedness rather than the one experienced during the time of GFC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2019) proposed a contagion mapping method to simulate the extensive exposure network of euro area banks. Le (2021) used SRISK to measure the systemic risks of 49 listed banks in six ASEAN countries and argued that the level of systemic risk between 2000 and 2018 was higher than that at the global financial crisis during 2007–2008. Dahir et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gorpe et al (2019) proposed a contagion mapping method to simulate the extensive exposure network of euro area banks. Le (2021) used SRISK to measure the systemic risks of 49 listed banks in six ASEAN countries and argued that the level of systemic risk between 2000 and 2018 was higher than that at the global financial crisis during 2007-2008. Dahir et al (2018) employed the system generalized method of moments (GMM) technique to examine the effects of funding liquidity risk and found that the liquidity risk is a risk factor which drives the potential bank default.…”
Section: Introductionmentioning
confidence: 99%
“…Cuối cùng là tỷ lệ vốn chủ sở hữu thông qua tỷ lệ vốn trên tổng tài sản (CAP i,t ). Tỷ lệ vốn chủ sở hữu thấp khiến cho các NHTM dễ chịu ảnh hưởng bởi các cú sốc rủi ro hệ thống hơn bởi tấm đệm vốn mỏng và mức độ nhạy cảm cao với các biến động của thị trường(Le, 2021) .4. Kết quả nghiên cứu 4.1.…”
unclassified